Preparasi dan karakterisasi fotokatalis NaTaO3 didoping ion lantanum (La/NaTaO3) dengan metode sol-gel - Husin, Husni (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Crystalline sodium tantalate doped with La3+ ions (La/NaTaO3) has been successfully synthesized by sol-gel technique. The photocatalysts have been prepared by mixing of TaCl5, NaOH, and La(NO3)3.2H2O in the aqueous solution of H2O2. The resulting materials are characterized by X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), and transmission electron microscopy (TEM) to provide useful information about crystallinity and morphology. All samples are exactly indexed as the pure NaTaO3 orthorhombic structure with the space group Pcmn. The XRD spectra displayed a single-phase NaTaO3 structure without any impurity phase, suggesting that lanthanum is uniformly incorporated into the NaTaO3 lattice. TEM images indicates that the particle sizes of the La-doped NaTaO3 powders are approximately 30-80 nm, while the particle sizes of the non-doped NaTaO3 are around 80-250 nm. Doping lanthanum in the NaTaO3 is able to prevent agglomeration, result in particle size, and better crystallinity. The La/NaTaO3 crystal structures reveal that a certain amount of lattice distortion due to the La3+ ions occupying the Na+ sites results in the increase of crystallite size. Powder formation mechanisms for both non-doped NaTaO3 and La-doped NaTaO3 are proposed based on the experimental results.Keywords: La-doped sodium tantalum oxide, photocatalyst, sol-gel, perovskite, orthorhombic